The Virtues of Disillusionment - Heighton, Steven (Athabasca University Press, 2020)
Most people go through life chasing illusions of success, fame, wealth, happiness, and few things are more painful than the reality-revealing loss of an illusion. But if illusions are negative, why is the opposite, being disillusioned, also negative? In this essay based on his inaugural writer-in-residence lecture at Athabasca University, internationally acclaimed writer Steven Heighton mathematically evaluates the paradox of disillusionment and the negative aspects of hope. Drawing on writers such as Herman Melville, Leonard Cohen, Kate Chopin, and Thich Nhat Hanh, Heighton considers the influence of illusions on creativity, art, and society. This meditation on language and philosophy reveals the virtues of being disillusioned and, perhaps, the path to freedom.